Cystoderma carpaticum (Basidiomycota, Agaricales), a rare fungus newly recorded from Croatia - Saar, Irja; Mešić, Armin; Tkalčec, Zdenko; Peintner, Ursula; Kušan, Ivana (Phytotaxa, 2016)
Cystoderma carpaticum was collected and originally described from the Carpathians in Poland. Later, it was recombined in the genera Lepiota and Echinoderma. Two recent collections from Croatia allowed for reliable phylogenetic and morphological comparative analyses of this rare fungus, including the holotype specimen. Our results confirmed that this taxon is a distinct species, and a member of the genus Cystoderma, not Lepiota nor Echinoderma (= Lepiota sect. Echinatae). C. carpaticum is re-described in detail, and data on its ecology and distribution are newly presented. Additional two studied collections of C. carpaticum (Austria, Czech Republic) were misidentified and they belong to C. subvinaceum. Synonymization of C. carpaticum with Leucopholiota decorosa is rejected.